2020
DOI: 10.1111/1471-0528.16530
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of qualitative and quantitative cranial ultrasonographic markers in first‐trimester screening for open spina bifida and other posterior brain defects: a systematic review and meta‐analysis

Abstract: Main results Twenty-three studies were included in our metaanalysis. The pooled sensitivity and specificity for qualitative assessment were 76.5% and 99.6%, and for quantitative assessment were 84.5% and 96.3%, respectively; specificity for the qualitative ultrasound signs was significantly higher (P = 0.001). The overall sensitivity of cranial sonographic markers for the screening of oPBD was 76.7% and specificity was 97.5%. Conclusions The qualitative approach demonstrated greater specificity, so this would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The present p.Lys56Serfs*6 variant is reported in 16 heterozygous carriers in the GnomAD database. A review of prenatal ultrasounds does not reveal any early onset signs suggesting a Joubert syndrome, such as enlargement of the fourth ventricle and cisterna magna and non‐visualization of the choroid plexus 6 . Based on the application of ACMG criteria, the CSPP1 truncating variant is a likely pathogenic/pathogenic variant; however, its relevance to the fetus's phenotype is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The present p.Lys56Serfs*6 variant is reported in 16 heterozygous carriers in the GnomAD database. A review of prenatal ultrasounds does not reveal any early onset signs suggesting a Joubert syndrome, such as enlargement of the fourth ventricle and cisterna magna and non‐visualization of the choroid plexus 6 . Based on the application of ACMG criteria, the CSPP1 truncating variant is a likely pathogenic/pathogenic variant; however, its relevance to the fetus's phenotype is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The metaanalysis by Rasmussenet al 16 reported that maternal obesity is associated with an increased risk of an NTD-affected pregnancy. A more recent meta-analysis by Zhang et al 17 suggested that maternal periconceptional obesity may be associated with an increased risk for spina bifida. Maternal underweight may be associated with increased risk for anencephaly.…”
Section: Discussionmentioning
confidence: 99%
“…These anomalies have traditionally been considered challenging to diagnose early in gestation, and it should be acknowledged that the use of a detailed first-trimester protocol to improve detection requires a high level of sonographer skill, the availability of high-resolution ultrasound equipment and appropriate allocation of time. Certainly, the role of sonographic markers in helping to identify at-risk fetuses should be acknowledged and merits further work, for example supporting the detailed examination of the posterior fossa for spina bifida 38 and the evaluation of multiple views of the fetal face for facial clefts. Most studies (n = 39) used a combination of TAS and TVS, making a meaningful comparison against those using only TAS (n = 9) difficult (Table S4).…”
Section: Factors Impacting Screening Performancementioning
confidence: 99%